Effect of antipyrine on the gastric emptying of liquid in rats - Soares,A.C.F. (2006)
Antipyrine (At) and dipyrone (Dp) delay gastric emptying (GE) in rats. The objective of the present study was to assess the effects of intravenous (iv) and intracerebroventricular (icv) administration of At and Dp on the GE of liquid by rats. GE was assessed in male Wistar rats (5-10 in each group) 10 min after the icv or iv drug injection by measuring percent gastric retention (%GR) of a saline test meal labeled with phenol red 10 min after administration by gavage. The At iv group was significantly higher (64.4 ± 2.6%) compared to control (33.4 ± 1.5%) but did not differ from the Dp group (54.3 ± 3.8%). After icv administration of At, %GR (34.2 ± 2%) did not differ from control (32.6 ± 1.9%), but was significantly higher after Dp (54.5 ± 2.3%). Subdiaphragmatic vagotomy significantly reduced %GR in the At group (30.2 ± 0.7%) compared to the sham group, but was significantly higher than in the controls (23.0 ± 0.5%). In the animals treated with At iv, baclofen significantly reduced %GR (28.3 ± 2.4%) compared to vehicle-treated animals (55.2 ± 3.2%). The same occurred in the animals treated iv with vehicle and icv with baclofen. Although vagotomy and baclofen reduced %GR per se, the reduction was twice more marked in the animals treated with At. The results suggest that At administered iv, but not icv, delays GE of liquid in rats with the participation, at least in part, of the vagus nerve and that this phenomenon is blocked by the activation of GABA B receptors in the central nervous system.